The Effect of Direct Feedback on Manuscript Development and Public Speaking Performance - Adys, Himala Praptami (Har Press Indonesia, 2025)
Public speaking remains a critical competency in business communication, yet many students struggle with performance anxiety and skill development. This study investigates the relationship between direct feedback on manuscript preparation and public speaking performance among 56 Business English Communication (BEC) students over one academic semester. Employing a quantitative quasi-experimental design, the research examined performance improvements following four systematic feedback interventions on speech manuscripts prior to mid-semester presentations. Results revealed statistically significant improvements in public speaking performance, with students demonstrating enhanced confidence, clarity, and delivery effectiveness. The findings suggest that structured manuscript feedback serves as a scaffolding mechanism that reduces anxiety while improving content organization and presentation skills. This research contributes to pedagogical approaches in business communication education by demonstrating the efficacy of iterative feedback processes in developing professional speaking competencies.